Host-specific functional compartmentalization within the oligopeptide transporter during the Borrelia burgdorferi enzootic cycle. - Ashley M Groshong (Public Library of Science (PLoS), 2021)
Borrelia burgdorferi must acquire all of its amino acids (AAs) from its arthropod vector and vertebrate host. Previously, we determined that peptide uptake via the oligopeptide (Opp) ABC transporter is essential for spirochete viability in vitro and during infection. Our prior study also suggested that B. burgdorferi employs temporal regulation in concert with structural variation of oligopeptide-binding proteins (OppAs) to meet its AA requirements in each biological niche. Herein, we evaluated the contributions to the B. burgdorferi enzootic cycle of three of the spirochete's five OppAs (OppA1, OppA2, and OppA5). An oppA1 transposon (tn) mutant lysed in the hyperosmolar environment of the feeding tick, suggesting that OppA1 imports amino acids required for osmoprotection. The oppA2tn mutant displayed a profound defect in hematogenous dissemination in mice, yet persisted within skin while inducing only a minimal antibody response. These results, along with slightly decreased growth of the oppA2tn mutant within DMCs, suggest that OppA2 serves a minor nutritive role, while its dissemination defect points to an as yet uncharacterized signaling function. Previously, we identified a role for OppA5 in spirochete persistence within the mammalian host. We now show that the oppA5tn mutant displayed no defect during the tick phase of the cycle and could be tick-transmitted to naïve mice. Instead of working in tandem, however, OppA2 and OppA5 appear to function in a hierarchical manner; the ability of OppA5 to promote persistence relies upon the ability of OppA2 to facilitate dissemination. Structural homology models demonstrated variations within the binding pockets of OppA1, 2, and 5 indicative of different peptide repertoires. Rather than being redundant, B. burgdorferi's multiplicity of Opp binding proteins enables host-specific functional compartmentalization during the spirochete lifecycle.